Sociocultural Influences on Poor Nutrition and Program Utilization of Mexico's Conditional Cash Transfer Program. (3rd December 2019) - Théodore, Florence L; Bonvecchio Arenas, Anabelle; García-Guerra, Armando; García, Ilian Blanco; Alvarado, Rocío; Rawlinson, Cloe J; Neufeld, Lynnette M; Pelto, Gretel H
ABSTRACT: Background: The impact of the Conditional Cash Transfer Program in Mexico was significant but smaller than expected. Several bottlenecks related to program design and implementation have been identified that may have limited its impact; population and other contextual factors may be equally important to analyze. Objectives: We aimed to explore how sociocultural context contributes to poor nutrition in Mexico and how it shaped the acceptability, fidelity, and penetration of the fortified food and of education sessions provided by the program. Methods: We carried out qualitative research studies in the central and southern states in urban, rural, and indigenous settings between 2001 and 2014 with different informants and by using interviews, focus group discussions, and nonparticipatory observation. We explored 4 dimensions of the sociocultural context: objective dimension (e.g., food availability and family organization), social norms and symbolic meaning related to child feeding, literacy and communication with the biomedical culture, and knowledge related to child care generally and child feeding. We generated information about the experience of the beneficiaries with fortified food and education sessions. Results: Several sociocultural factors, including patriarchal family organization, high availability of nonnutritious food, social norms promoting the consumption of food in liquid form for young children, sharing of food among family members, traditional knowledge, and communication barriers with the biomedical culture, participated in shaping the poor nutrition situation, the inadequate utilization of fortified foods, and the inappropriateness of the education sessions. Conclusions: Our studies revealed the importance of local context and culture to understand the acceptance, utilization, and impact of a nutrition program and shed light on infant and child feeding practices. This knowledge is critical to strengthen program designs and ensure adequacy with the diversity of cultural and social contexts in which programs are implemented.